(untitled) (International Seven Journal of Multidisciplinary, 2025)
Amelogenesis imperfecta (AI) is a hereditary disorder that compromises the formation of dental enamel, affecting function, esthetics, and patients’ quality of life. This narrative review aimed to synthesize the main restorative and functional strategies described in the literature for managing AI. The literature search was conducted in the PubMed database, prioritizing publications from the past five years. The analyzed studies show that, in primary and mixed dentition, provisional treatment with stainless-steel crowns and direct restorations is essential to protect dental structure and preserve the vertical dimension of occlusion. In adolescents and young adults, direct and indirect restorative options, such as prefabricated veneers and ceramic crowns, provide good esthetic and functional outcomes. In more complex cases, full-mouth rehabilitation with an increased vertical dimension—especially using lithium disilicate crowns—demonstrates high predictability and durability. The literature also highlights the importance of a multidisciplinary approach and longitudinal planning. It is concluded that AI treatment must be individualized, considering age, phenotype severity, and functional demands, prioritizing structural preservation, esthetics, and full restoration of oral function.